An application of charge-coupled Device (CCD) tomography system for gemological industry - a review - Fatinah, Mohd Rahalim; Juliza, Jamaludin; Syarfa Najihah, Raisin; Wan Zakiah, Wan Ismail; Irneza, Ismail; Ruzairi, Abdul Rahim; Yasmin, Abdul Wahab (Springer Science and Business Media Deutschland GmbH, 2022)
Charge-Coupled Device (CCD) is a semiconductor chip with a light-sensitive sensor. The CCD has been used in many fields of engineering, including astronomy, medical sciences and processing. CCD is capable to detect light sources and convert this analogue signal into electrical signal. CCD is an integrated circuit that contains a large number of small photo elements with high sensitivity to light energy. The main focus of this research paper is on the review of CCD basic operating principle and construction, CCD characteristic, and the application of CCD in tomography system. The potential use of CCD in the gemological industry is also highlighted in this paper. Gemology is one of the important industries that considered profitable and crucial that deals with precious stones. This industry is in need of standardized grading valuation of gemstones as the current technique is prone to errors. An approach to the standardized grading technique is proposed where CCD tomography is used to detect and analyze the light distribution characteristic in ruby stones.